Pergeseran Fungsi Pura di Bali: Dari Ritual ke Pertemuan Politik - A.A Sagung Ngurah Indradewi (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
This article tries to assert the focus of discussion on the function of temples in Bali that shifts to sociological and political functions. The external pressure sociological and political dimensions are assumed to be able to shift or to complete the function of the temple as a place of worship for Hindus in Bali. The sociological function of temple is as a means of reunion for Hindus who live far from their family and the political function is the temple can be used as a place to hold political meetings by political leaders who will participate in local elections. Can the temple functions be shifted? Six informants who are considered being the most competent to answer this question stated “not” because it is due to a political meeting included giving donation for the temple maintenance and helping to finance such a big scale ceremony of Hindus in Bali.